Pengaruh Pengalaman, Kompetensi, Independensi dan Fee Audit pada Kualitas Audit - Sisna Armawan, I Putu; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 30 No 5 (2020)DO - 10.24843/EJA.2020.v30.i05.p11, 2020)
The research aims to obtain empirical evidence of the effect of experience, competence, independence, and audit fees on audit quality. This research was conducted at a Public Accountant Office in Bali registered in IAPI (Institut Akuntan Publik Indonesia) 2019. The method of determining the sample uses non-probability sampling techniques. The number of samples in this study were 48 auditors. The data collection method uses a questionnaire. The analysis technique used is multiple linear regression. The results showed that experience, competence, independence and audit fees had a positive effect on audit quality. Keywords: Experience; Competence; Independence; Audit Fees; Audit Quality.